Revitalizing Islamic Civilization Through Scientific Traditions: A Contemporary Analysis of Said Nursi’s Thought - Achmad Reza Hutama Al Faruqi; Nabila Huringiin; Moh. Isom Mudin; Zahin Zahid Faza; Mohamed Hedi Ouannes (Journal of Islamic and Social Studies, 2026)
This study explores the philosophical and socio-intellectual reconstruction of Islamic civilization in the modern era through the thought of Bediuzzaman Said Nursi. The purpose of this research is to analyze how Nursi’s theological and epistemological framework provides a constructive response to the challenges of secular modernity, materialism, and moral disintegration within Muslim societies. Employing a qualitative method with a philosopical approach and content analysis method, this study critically examines Nursi’s primary texts—particularly the Risale-i Nur Collection—and contextualizes them within broader discourses of Islamic renewal and modernity. The findings reveal that Nursi’s concept of iman tahqiqi (verified faith) and his integration of reason and revelation serve as the foundation for reconstructing a spiritually rooted yet intellectually open Islamic civilization. His vision emphasizes moral reform, scientific advancement guided by divine purpose, and social cohesion based on justice and compassion. Moreover, Nursi’s approach bridges traditional religious scholarship with modern epistemology, offering a model for holistic development that reconciles faith, knowledge, and progress. The study concludes that Nursi’s thought remains profoundly relevant to contemporary Muslim societies facing crises of identity, secularization, and environmental degradation. It recommends further comparative research between Nursi’s civilizational vision and contemporary Islamic thinkers to formulate an integrative paradigm for Islamic civilization renewal in the 21st century.